Marketing Strategy Planning of Kahyangan Coffee Using Marketing Mix in Coffee Shops - Lestari, Dwi Indah; Amilia, Winda; Rusdianto, Andrew Setiawan; Choiron, Miftahul; Mahardika, Nidya Shara (University of Jember, 2023)
Kopi Kahyangan continues to develop its product quality and market through the preparation of marketing strategies based on the marketing mix theory. This study aims to determine the marketing strategy of Kahyangan coffee based on the marketing mix in increasing sales volume. This study used a quantitative descriptive approach method using SWOT analysis, QSPM, and questionnaire tests using validity and reliability tests. The tools used to test this study were Statistical Product and Service Solution (SPSS) 25, Microsoft Excel, and Microsoft Word. The types and sources of data used are primary data and secondary data. The analysis method used is a descriptive analysis of marketing strategies that refers to the concept of the 4P Marketing mix (product, price, promotion, and place) using SWOT analysis (Strength, Weakness, Opportunity, and Threat) and QSPM (Quantitative Strategic Planning Matrix) matrix analysis. The results of the marketing strategy planning analysis according to the company's position in the IE matrix can use market penetration strategies by improving product quality, market development by increasing promotions and reaching new segments, and product development by making Kahyangan Coffee product innovations to increase sales volume of Kahyangan Coffee. The priority strategy of marketing strategy planning is to maintain quality and increase product licenses.